2017
DOI: 10.25110/arqvet.v20i3.2017.6692
|View full text |Cite
|
Sign up to set email alerts
|

ÓLEO ESSENCIAL DAS FOLHAS E FRUTOS DE Schinus terebinthifolius RADDI NO CONTROLE DE Pratylenchus zeae

Abstract: BORDIN, J. C.; BORTOLUCCI, W. de C.; CARPI, M. C. G.; ANDRÉ, V. C. S.; PACCOLA-MEI-RELLES, L. D.; GOMES, S. de M. S. Óleo essencial das folhas e frutos de Schinus terebinthifolius Raddi no controle de Pratylenchus zeae. Arq. Ciênc. Vet. Zool. UNIPAR, Umuarama, v. 20, n. 3, p. 153-159, jul./set. 2017. RESUMO:Os óleos essenciais (OEs) são metabólitos secundários que podem apresentar potencial no controle alternativo de nematoides. Assim objetivou-se testar o OE de pimenta rosa no controle de P. zeae em condições… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Little is known about the properties of this plant in reducing plant-parasitic nematodes. In one of the few studies, Schwengber et al (2017) reported the effect of the essential oil of this plant against Pratylenchus zeae in the greenhouse. Borges et al (2018) also related to the suppression of root-knot nematode by S. terebinthifolius essential oil.…”
Section: Gomes Va Et Almentioning
confidence: 99%
“…Little is known about the properties of this plant in reducing plant-parasitic nematodes. In one of the few studies, Schwengber et al (2017) reported the effect of the essential oil of this plant against Pratylenchus zeae in the greenhouse. Borges et al (2018) also related to the suppression of root-knot nematode by S. terebinthifolius essential oil.…”
Section: Gomes Va Et Almentioning
confidence: 99%
“…For plants, essential oil and oleoresin present an important defense mechanism, as they contain capsaicin, with antifungal, bactericidal, antiviral, insecticidal, larvicidal and molluscicidal action (Pereira et al, 2016;Tomazoni et al, 2017;Schwengber et al, 2017).…”
Section: Introductionmentioning
confidence: 99%